Transformational model of the healthcare market in Ukraine in the conditions of modern challenges - Melnyk, Alla (Herald of Economics, 2022)
Introduction. Reforming the health care system in Ukraine, dismantling its old economic model, the emergence and development of entrepreneurship in this type of economic activity, which took place in recent years, led to a new nature of economic relations. The health care system of Ukraine faces the formation of a competitive environment, the need to characterize itself through the prism of its diagnosis as a kind of market. Both the system of public management of the industry and the influence of new opportunities and threats management on the system of the health care institutions should be taken into account. Given the current challenges, significant uncertainty, dynamic changes, this highlights the need for in-depth systematic theoretical and methodological analysis of the specifics of the model of the created market, identifying the degree of its adaptability to the needs of restoring or maintaining public health. Additionally, health care system management requires attention to the development of scientific and methodological framework for this task.Purpose. The purpose of the article is a theoretical and methodological assessment of the process of market formation in the health care system, its impact on the nature of the health care system in today’s challenges and recommendations for adjusting public policy and mechanisms for its implementation in multilevel governance.Methods. The method of comparative analysis was used to compare health care systems and models of the health care market in Ukraine and the world; systematic analysis allowed to determine the components of the health care market at the macro and meso levels, pest analysis - to identify factors influencing the development of health care market segments and factors that indicate the need for regulatory influence of public authorities, hospital management; institutional and comparative analysis - to identify the institutional environment of market actors; SWOT-analysis and expert assessments - to assess internal and external environment of competition, setting goals and strategic priorities.Results. Having analyzed the theoretical basis, the author’s approach to the interpretation of the essential characteristics of the model of the healthcare market in Ukraine is formed. The current state, features of the market, factors of internal and external environment of health care facilities in Ukraine are assessed, and the problems are identified. The model of the healthcare market in the country is interpreted by the author as: a) transformational, due to a number of factors, primarily the incompleteness of health care reform; b) the model of different speeds, which is caused by the different degree of development of individual market segments, the spread of externalities to them, etc. The current regulatory policy is analyzed, the factors of actualization of the problem of implementation of strategic planning at the present stage are revealed and the necessity of its implementation in management of the relevant public authorities and market participants is proved.Discussion. The issues of organizational support of the functioning of the health care market during the war and post-war reconstruction, formation of the methodological base for adjustment and implementation of strategies for the development of health care systems in the regions, strategies of medical institutions, organization of strategies, overcoming resistance to change deserve further research.